Kinetic growth of copper oxidation in semiconductor packaging / Siti Rahmah Esa - Siti Rahmah , Esa (2017)
This thesis systematically investigates the physical, mechanical and chemical properties of the copper oxidation on the copper alloy leadframe that influence the reliability of an IC packaging in semiconductor industries. In this study, the oxidation on the copper alloy leadframe was promoted via heat treatment process. The copper oxidation was investigated and characterized using various advanced analytical techniques by means of Optical Microscopy, Field Emission Scanning Electron Microscopy (FESEM), Atomic Force Microscopy (AFM), Vickers Micro-Indentation, Energy Dispersive X-ray Spectroscopy (EDS), Auger Electron Spectroscopy (AES), Focused Ion Beam (FIB), High Resolution Transmission Electron Microscopy (HRTEM) and Energy Electron Loss Spectroscopy (EELS). The oxidation was found to cause a transformation of physical colour of the leadframe from light brown to dark brown. The changes of the surface texture from fine to coarse granular were also observed as a result of the oxidation process. The coarse granular surface derived from high temperature treatment was found to be hard and brittle resulting to the flaky and crack surface as it is induced by the Vickers micro indentation test. The oxidation was found to be initiated at the heat treatment temperature of 120 °C. The copper oxide thickness shows an increasing trend as the temperature increases. The copper oxide thickness growth was 16 nm, 49 nm, 93 nm and 160 nm at the heat treatment temperature of 150 °C, 180 °C, 210 °C and 240 °C respectively. The activation energy was found to be 41 kJ/mol. At high oxidation temperature, the formation of micro-voids and separations were observed along the interface between the copper oxide and the bulk copper leadframe. Poor adhesion at this interface region due to micro-voids and separation were found to be the root cause of the delamination issue. EELS analysis determined that for the regions with intact interface the oxidation system is CuO/Cu2O/CuO/Cu, however, in regions containing micro-voids or separations the oxidation system is found to be CuO/Cu2O/Cu.